2003
DOI: 10.1007/s00234-003-1019-8
|View full text |Cite
|
Sign up to set email alerts
|

Determination of indices of the corpus callosum associated with normal aging in Japanese individuals

Abstract: Indices of the corpus callosum with normal aging and their sex differences were elucidated using quantitative MRI. We studied 94 Japanese men (mean+/-SD 57.3+/-20.8 years, range 6-90 years) and 111 Japanese women (mean+/-SD 61.2+/-17.6 years, range 9-86 years) who had no intracranial lesions on MRI and no history of neurological illness. The widths of the rostrum, body and splenium, the anterior to posterior length, and the maximum height in the midsagittal image were selected for measurement. The Evans index,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
49
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 25 publications
13
49
3
1
Order By: Relevance
“…There was a statistically significant difference in the midsaggital area between right handed and left handed [14] 661±9 663±7 Kertesz et al [16] 724* 716* Clarke et al [5] 540* 550* Pujol et al [19] 577±115 582±91 Hardan et al [15] 671±100** Mostofsky et al [25] 627±73** Oka et al [18] 657±80** Laissy et al [17] 636** Suganthy et al [7] 700±84* *Sd Not Presented **No Gender Specified subjects (p=0.048). Also, there was a statistically significant difference in r3 distance between those using their right hand and those using their left hand in cleaning the blackboard (p=0.041) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was a statistically significant difference in the midsaggital area between right handed and left handed [14] 661±9 663±7 Kertesz et al [16] 724* 716* Clarke et al [5] 540* 550* Pujol et al [19] 577±115 582±91 Hardan et al [15] 671±100** Mostofsky et al [25] 627±73** Oka et al [18] 657±80** Laissy et al [17] 636** Suganthy et al [7] 700±84* *Sd Not Presented **No Gender Specified subjects (p=0.048). Also, there was a statistically significant difference in r3 distance between those using their right hand and those using their left hand in cleaning the blackboard (p=0.041) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[14,21] Several studies reported that the measurements of the anterior parts of the corpus callosum (rostrum, genu and anterior parts of the trunk) were decreased during normal aging. [7,[22][23][24][25] Takeda et al reported that the widths of rostrum, body and splenium of the corpus callosum became thinner with age. [25] Suganthy et al [7] reported that the length of the corpus callosum increased with age and regression equations for predicting age was derived from the length of the corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater thickness of the corpus callosum in these regions may be linked to an increased number of interhemispheric fiber connections, leading to a higher inter-hemispheric value in these areas, given the splenium is anatomically related to the parietal and occipital regions [21][22][23][24] . Studies employing new magnetic resonance techniques such as tractography, may be able to shed further light on these issues.…”
Section: Discussionmentioning
confidence: 99%
“…[20] uzunluk artışına ek olarak yükseklik artışı da gözlemlemişlerdir. Bizim çalışmamızda yaş ile KK uzunluğu ve A açısı arasında pozitif korelasyon saptanmasına rağmen daha geniş serilere ihtiyaç vardır.…”
unclassified